Regulatory and Tax Treatment of Loan Loss Provisions - Dziobek, Claudia (Washington, D.C. : International Monetary Fund, 1996)
Provisioning for loan losses is a method for recognizing the reduction in the value of a hank's loan portfolio. Provisions are an essential element of prudential risk management and capital adequacy measurement and an important market signal. Loan loss provisions constitute a normal operating expense and should be deducted from taxable income provided that banks adhere to consistent and strictly enforced provisioning procedures, and provided that these mirror loan default probabilities. The argument for harmonized regulatory and tax treatment of loan loss provisions can be based on the economic similarity between loan losses and depreciation of machines and equipment. Tax deductibility of loan loss provisions does not imply a tax deferral or a special subsidy for banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet